2020
DOI: 10.1186/s13567-020-00785-x
|View full text |Cite
|
Sign up to set email alerts
|

Precise location of linear epitopes on the capsid surface of feline calicivirus recognized by neutralizing and non-neutralizing monoclonal antibodies

Abstract: We report the generation, characterization and epitope mapping of a panel of 26 monoclonal antibodies (MAbs) against the VP1 capsid protein of feline calicivirus (FCV). Two close but distinct linear epitopes were identified at the capsid outermost surface (P2 subdomain) of VP1, within the E5′HVR antigenic hypervariable region: one spanning amino acids 431-435 (PAGDY), highly conserved and recognized by non-neutralizing MAbs; and a second epitope spanning amino acids 445-451 (ITTANQY), highly variable and recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…We have developed a system for the generation of VLPs derived from different caliciviruses, such as swine norovirus [ 42 ], feline calicivirus [ 43 ] and RHDV [ 25 ]. Our previous results have shown that RHDV VLPs can be produced to high yields, are highly immunogenic and are suitable to be used as diagnostic reagents or vaccines for the control of RHDV in rabbits [ 24 , 41 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a system for the generation of VLPs derived from different caliciviruses, such as swine norovirus [ 42 ], feline calicivirus [ 43 ] and RHDV [ 25 ]. Our previous results have shown that RHDV VLPs can be produced to high yields, are highly immunogenic and are suitable to be used as diagnostic reagents or vaccines for the control of RHDV in rabbits [ 24 , 41 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The B-cell epitopes: FCV22 (GSGNDITTANQYDAADIIRN), derived from FCV capsid protein [27], and 2L21 (SDGAVQPDGGQPAVRNERATGS), derived from CPV VP2 protein [29], were prepared as synthetic peptides by solid phase synthesis and HPLC purification (D. Andreu, Pompeu Fabra University, Barcelona, Spain), and were used in ELISA assays to detect specific antibody titers.…”
Section: Peptides Virus Cells and Micementioning
confidence: 99%
“…For Western blot analyses, proteins were transferred from gels onto polyvinylidene difluoride (PVDF) membranes using Trans-Blot ®® Turbo™ Transfer System (Bio-Rad Laboratories, Hercules, CA, USA). Membranes were saturated (overnight, 4 • C) with PBS, 5% (wt/vol) skim milk, and 0.5% (vol/vol) Tween 20 and incubated (1 h, 37 • C) with either a rabbit hyperimmune serum against RHDV to detect VP60 protein, 51D10 monoclonal antibody recognizing FCV22 epitope [27], or 3C9 monoclonal antibody against 2L21 epitope [28]. After several washes with PBS-0.05% Tween 20, membranes were incubated (1 h, 37 • C) with HRP-conjugated goat anti-rabbit IgG (Thermo Fisher Scientific, Waltham, MA, USA) or HRP-conjugated goat anti-mouse IgG (Invitrogen, Carlsbad, CA, USA).…”
Section: Western Blot Analysesmentioning
confidence: 99%
See 2 more Smart Citations